Pemberdayaan Satuan Petugas Unit Kesehatan Sekolah Kesehatan Reproduksi Remaja dalam Pemanfaatan Olahan Daun Kelor sebagai Langkah Preventif Anemia - Putri Ramadhanti, Indah; Nova H, Desri; Ramadanti, Tika; Fransiska, Mellia; Fakhri, Ikhtiarina; Robiatul Khaira, Puja (Poltekkes Kemenkes Surakarta, 2024)
Background: Anemia is a priority health problem for adolescents with a prevalence of 17% in Bukittinggi City in 2023, the highest case at the Rasimah Ahmad Health Center at 28.5%. Government programs, namely the provision of iron tablets and the existence of school health units, have not optimally reduced the prevalence of anaemia in adolescents. The iron content of moringa leaves increases haemoglobin. The formation of SHU ARH officers to prevent anaemia and training in processing moringa leaves aims to be an innovation in the School Health Service programme to serve reproductive health problems in overcoming anaemia to prevent the impact of non-compliance with iron tablet consumption. Methods: Collaboration partners are SMPN 03 Bukittinggi City and Rasimah Ahmad Health Center Bukittinggi City from June to September 2024. We collect data through interviews, observations, and documentation. Five methods are used: socialization, preliminary studies and advocacy; formation and training of the SHU ARH Task Force for adolescents; providing education, mentoring and providing processed moringa leaves; and evaluating the sustainability of the SHU ARH. Results: the achievement of the target: 1) The formation of the SHU ARH consisting of 18 people; 2) Of the 87 young women, 79% have high knowledge of anaemia and the benefits of processed moringa leaves, 78% apply processed moringa leaves at home, and cases of anaemia decreased by 20.66%. Conclusion: The sustainability of the programme by providing moringa leaf seeds and planting in schoolyards as a step to provide raw materials for processed moringa leaves.